An augmented productivity of solar distillers integrated to HDH unit: Experimental implementation. (25th February 2020) - Abdullah, A.S.; Omara, Z.M.; Bek, M.A.; Essa, F.A.
Research highlights: Effects of the wooden cellulose and aspen pad performance as packing materials. Draining the brine excess hot water vapor from wick solar stills to feed the humidifier. Cellulose paper with forced circulation gave higher distillate than the natural circulation by 34%. GORa of the hybrid system is 7.6. The water flow rate of 4 kg/min gave the best results. Abstract: A hybrid system of HDH and six wick stills was conducted to scrutinize the achievement of the system under different considerable conditions. Wooden cellulose and aspen pad were chosen as packing materials. Besides, different water flow rates (1, 2, 3, and 4 kg/min) were examined. Also, natural and forced air circulation with different fan speeds (500, 1000, and 1500 rpm) were investigated. The warm water exhausted from HDH was utilized to feed the wick distillers. A fan was fixed at the distillers' backside to condensate the excess vapor from the stills in dehumidifier. Results revealed that the cellulose paper provided higher productivity than the aspen pad. Besides, the optimal values of the water flow rate and the fan speed (causing air flow rate) are 4 kg/min and 1500 rpm, respectively. Moreover, when using the cellulose paper, the forced air circulation produced higher productivity than the natural circulation by 34%. The existence of condenser only improved the distillate by 16.6% compared to 3% improvement due to providing vapor drain only. At 4 kg/min, GORa of the hybrid system was 7.6 when using the condenser and providing a drain compared to 7.3 and 6.1 for the system with a condenser only and without any modifications, respectively.